Cervical pedicle morphometry in a Latin American population: A Brazilian study. Issue 25 (June 2016) - Herrero, Carlos Fernando; Luis do Nascimento, Anderson; Maranho, Daniel Augusto Carvalho; Ferreira-Filho, Narcélio Mendes; Nogueira, Carolina Pinto; Nogueira-Barbosa, Marcello Henrique; Defino, Helton Luis Aparecido
Abstract : Abstract: The goal of this study was to conduct a detailed computed tomography (CT) assessment in the Brazilian population of the screw starting point, trajectory, and dimensions of pedicle in the cervical spine. Two hundred consecutive patients were retrospectively evaluated using cervical spine CT, with imaging reconstruction of each cervical vertebrae in the axial plane with 2 mm, and in sagittal reconstructions with 3 mm. Parameters in axial plane included the pedicle width (PW), pedicle axis length (PAL), pedicle transverse angle (PTA), and the distance from the entry point to the point between the lamina and spinous process (DEP). Measurements in the sagittal plane involved the pedicle height (PH) and the pedicle sagittal angle (PSA). The mean PW and PH were smaller in females than in males in all cervical vertebrae, but there were no significant differences of PTA among genders. PSA ranged from 15.2° to 23.7°. Mean values of PAL and DEP had a tendency to decrease from the proximal to distal cervical vertebrae. PW was <4 mm in 7.5% of men (C3) and 25% of women (C3), and <4.5 mm in 20% (C3 male) and 66% (C3 female). The intra- and inter-observer reliability were very good for the tomographic measurement of PW, and good for PH. For PAL, the intraobserver reliability was good, but the interobserver reliability varied from moderate to good. Considering PTA and PSA, the intraobserver reliability was good, but the interobserver reliability moderate for PTA and poor or fair for PSA. DEP measurements showed poor intraobserver reliability, and poor or moderate interobserver reliability. Our results presented similar trend of previous studies, but the frequency of patients with PW <4.5 mm in our population is higher, suggesting an increased risk during the attempting of transpedicular screw technique.